Maternal provisioning and zygotic activation: transcriptomic dynamics of early atlantic halibut (Hippoglossus hippoglossus) embryogenesis - Niepagen, Nils; Bertolini, Francesca; Berg, Leif; Tomkiewicz, Jonna; Kjørsvik, Elin (Frontiers in Cell and Developmental Biology, 2025)
IntroductionIn Atlantic halibut (Hippoglossus hippoglossus) aquaculture, egg and larval quality remain major bottlenecks. Most transcriptomic and proteomic studies compare freshly fertilized eggs of good versus poor quality, assuming early molecular differences explain hatching success. However, many lethal phenotypes arise only after the mid-blastula transition (MBT), suggesting that early comparisons may overlook key developmental processes.MethodsWe performed stage-resolved RNA sequencing of Atlantic halibut embryos spanning unfertilized egg (UF), cleavage (8C, 16C), blastula (BL), 25% epiboly (25 EB), and blastopore closure (50 degree-days, 50 dd). Differential expression analysis (DESeq2 with LFC shrinkage), Gene Ontology (GO) overrepresentation (PANTHER, REVIGO), and curated axis-patterning gene sets from zebrafish orthologs were used to map transcriptional dynamics.ResultsMinimal transcriptional change occurred during cleavage (UF–16C), dominated by maternal transcripts. A pronounced transcriptional shift emerged at MBT (16C→BL), marked by upregulation of canonical developmental pathways (Wnt, BMP, Notch) and axis-specification genes (e.g., bmp2b, chrd, wnt8b, fgf8a). These pathways remained active through gastrulation (BL→25 EB), alongside enrichment of morphogenetic processes such as mesoderm formation and left–right symmetry. By 50 dd, expression shifted toward lineage differentiation programs involving neurons, muscle, and cranial skeleton. Axis-regulator dynamics showed that dorso–ventral (D–V) patterning is initiated by maternal factors but reinforced by zygotic cascades, whereas anterior–posterior (A–P) patterning is primarily zygotic.DiscussionOur results demonstrate that the decisive transcriptional programs underlying axis formation and organogenesis are activated from MBT onward. These findings imply that comparisons limited to unfertilized or early cleavage stages cannot capture the biology determining embryo viability. Stage-resolved analyses encompassing MBT and gastrulation are therefore essential for identifying transcriptomic markers of egg and larval quality in halibut.